ANDROID SHORTCUT APPLICATION DEV ANDROID SHORTCUT APPLICATION DEVELOPMENT AS A MEDIUM FOR RELIGIOUS INFORMATION USING THE APPSGEYSER PLATFORM : ANDROID SHORTCUT APPLICATION DEVELOPMENT AS A MEDIUM FOR RELIGIOUS INFORMATION USING THE APPSGEYSER PLATFORM - Nurkaif; Imam Mualim; Nuari Anisa Sivi; Rena Nainggolan; Fenina Adline Twince Tobing (IJNMT (International Journal of New Media Technology), 2025)
The development of information and communication technology has encouraged the use of mobile devices as a medium for disseminating information, including in the religious field [10]. Today's society requires fast, practical, and easy-to-use access to religious information through Android-based smartphones [6]. This study aims to develop a shortcut-based Android application as a medium for religious information by utilizing the AppsGeyser platform [7]. The development method used includes needs analysis, application design, implementation, and functional testing of the application using a Research and Development (R&D) approach [3]. The results of the study indicate that the Android shortcut application is able to present religious information effectively, is easily accessible, and is lightweight to use without requiring high device specifications.